Low Barrier Tele-Buprenorphine in the Time of COVID-19: A Case Report. Issue 4 (July 2020) - Harris, Miriam; Johnson, Samantha; Mackin, Sarah; Saitz, Richard; Walley, Alexander Y.; Taylor, Jessica L.
Abstract : Background: To reduce the spread of coronavirus disease 2019 (COVID-19), many substance use disorder treatment programs have transitioned to telemedicine. Emergency regulatory changes allow buprenorphine initiation without an in-person visit. We describe the use of videoconferencing for buprenorphine initiation combined with street outreach to engage 2 patients experiencing homelessness with severe opioid use disorder (OUD). Case Presentation: Patient 1 was a 30-year-old man with severe OUD who had relapsed to injection heroin/fentanyl after incarceration. A community drop-in center outreach harm reduction specialist facilitated a videoconference with an addiction specialist at an OUD bridge clinic. The patient completed a community buprenorphine/naloxone initiation and self-titrated to his prior dose, 8/2 mg twice daily. One week later, he reconnected with the outreach team for a follow-up videoconference visit. Patient 2, a 36-year-old man with severe OUD, connected to the addiction specialist via a syringe service program harm reduction specialist. He had been trying to connect to a community buprenorphine/naloxone provider, but access was limited due to COVID-19, so he was using diverted buprenorphine/naloxone to reduce opioid use. He was restarted on his previous dose of 12/3 mg daily which was continued via phone follow-up 16 days later. Conclusions: COVID-19-related regulatory changes allow buprenorphine initiation via telemedicine. We describe 2 cases where telemedicine was combined with street outreach to connect patients experiencing homelessness with OUD to treatment. These cases highlight an important opportunity to provide access to life-saving OUD treatment for vulnerable patients in the setting of a pandemic that mandates reduced face-to-face clinical interactions.